2021
DOI: 10.3390/vaccines9111358
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy and Attitude toward Booster Doses among US Healthcare Workers

Abstract: Vaccine reluctance among healthcare workers (HCW) can have widespread negative ramifications, including modeling behavior for the general population and challenges with maintaining a healthy workforce so we can respond to a resurgence of the pandemic. We previously reported that only one-third of HCW were willing to take the vaccine as soon as it became available prior to its Emergency Use Authorization (EUA). Here, we re-examine the attitude toward COVID-19 vaccines among HCW several months after the vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
99
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 23 publications
14
99
2
2
Order By: Relevance
“…The association with the gender is in accordance with previous studies across different countries [10,[31][32][33] and may be explained by the fact that the spread of the COVID-19 in Italy has affected females slightly more than males, although the mortality rate was higher for males. Moreover, those older were more likely to accept the booster, which is consistent with prior studies on this vaccination [10,12,34]. This finding is not surprising and it may be because of the fact that older people are at higher risk of severe disease from infection of COVID-19.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The association with the gender is in accordance with previous studies across different countries [10,[31][32][33] and may be explained by the fact that the spread of the COVID-19 in Italy has affected females slightly more than males, although the mortality rate was higher for males. Moreover, those older were more likely to accept the booster, which is consistent with prior studies on this vaccination [10,12,34]. This finding is not surprising and it may be because of the fact that older people are at higher risk of severe disease from infection of COVID-19.…”
Section: Discussionsupporting
confidence: 87%
“…A notable finding was that the hesitancy towards the booster dose was low among the responders since 24.7% of the sample were classified as hesitant with a total VHS score ≥25. Other surveys have found varying proportions of participants willing to receive the booster dose with values of 55.3% among HCWs in Saudi Arabia [13], 61.8% in adult Americans [14], 71% among adults in Poland [10], 71.3% among HCWs in Czechia [15], 83.6% a hypothetical yearly booster vaccine among healthcare workers in the United States [12], 84.5% among medical students in Japan [11], and 91.1% in the general population in China [16]. In the present study interviewees highlighted that the most common reasons in vaccine-related decision-making were because they would protect themselves and their relatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acceptance of the third dose of COVID-19 vaccine varied among different countries. For healthcare workers in the United States, the overall acceptance rate for a booster vaccination was 83.6% [13]. In addition, it was high (71.3%) among healthcare workers in Czechia, while 12.2% remained undecided and 16.6% opposed [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sugawara et al revealed in 2021 that 89.1% of Japanese medical students were positive about a booster vaccination [16]. The main reasons against receiving included side effects after previous doses, a perception that further vaccination was not necessary, and the distrust of regulatory agencies (45.3%), government (48.6%) and drug companies (50%) [13,15].…”
Section: Introductionmentioning
confidence: 99%